1997
DOI: 10.1046/j.1365-2141.1997.4233234.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the cytogenetic abnormality +i(3)(q10) in persistent polyclonal B‐cell lymphocytosis: a FICTION study in three cases

Abstract: Persistent polyclonal B‐cell lymphocytosis (PPBL) is a rare entity characterized by a moderate but sustained lymphocytosis where some binucleated or bilobulated circulating forms constitute, even if they are not entirely specific, the cytological hallmark of the disease. An additional chromosome long arm i(3)(q10) has recently been reported as a recurrent cytogenetic aberration, contrasting with a usual polyclonal immunoglobulin expression. To determine more precisely the distribution of the chromosomal abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…More recently, Callet-Bauchu and colleagues have reported three additional subjects with PPBL; +i(3q) was observed in 6-12% of metaphase cells in all three patients after stimulation with TPA. 5 These findings were also confirmed by FISH analysis. Using a technique of simultaneous fluorescence immunophenotyping and interphase cytogenetics (FICTION) they demonstrated that the +i(3q) was restricted to B lymphocytes and present in both binucleated and non-binucleated lymphocytes.…”
Section: The Editorsupporting
confidence: 74%
“…More recently, Callet-Bauchu and colleagues have reported three additional subjects with PPBL; +i(3q) was observed in 6-12% of metaphase cells in all three patients after stimulation with TPA. 5 These findings were also confirmed by FISH analysis. Using a technique of simultaneous fluorescence immunophenotyping and interphase cytogenetics (FICTION) they demonstrated that the +i(3q) was restricted to B lymphocytes and present in both binucleated and non-binucleated lymphocytes.…”
Section: The Editorsupporting
confidence: 74%
“…Among the cases reported in the literature, one patient developed a malignant pulmonary blastoma 11 years after diagnosis, 32 another patient developed a large-cell lymphoma 19 years after initial PPBL diagnosis 33 and one patient presented concomitantly polyclonal lymphocytosis and malignant gastric non-Hodgkin's lymphoma. 31 With a 3.6 years follow-up, we did not observe any lymphoproliferative disease.…”
Section: Cytogenetics Analysismentioning
confidence: 59%
“…These genetic aberrations were found to be restricted to B cells (PPBL and normal lymphocytes), indicating the presence of a contrasting restricted cytogenetic population in PPBL patients. 31 The long and indolent evolution in most patients showing multiple t(14;18) translocations confirms that this rearrangement is not sufficient to confer tumorigenicity, even though Bcl-2 is a well-recognized proto-oncogene. Among the cases reported in the literature, one patient developed a malignant pulmonary blastoma 11 years after diagnosis, 32 another patient developed a large-cell lymphoma 19 years after initial PPBL diagnosis 33 and one patient presented concomitantly polyclonal lymphocytosis and malignant gastric non-Hodgkin's lymphoma.…”
Section: Cytogenetics Analysismentioning
confidence: 94%
“…The lymphoproliferation had characteristics common to both the B-cell lymphocytosis associated with partial trisomy 3 and very low grade subtypes of MZBC lymphomas. [12][13][14] The splenomegaly and elevated LDH that responded to IFN therapy were suggestive of splenic lymphoma. The monoclonal B cells had MZBC markers and were WA ϩ ; 25% or more of B-cell lymphomas associated with HCV-type II cryoglobulinemia arise from WA ϩ B cells although correlation with MZBC markers has not been assessed.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] Further studies are needed to determine the prevalance of these abnormalities in HCV infection with and without type II cryoglobulimenia and their possible physiologic and/or pathophysiologic implications.…”
mentioning
confidence: 99%